Finite temperature behavior of carbon atom-doped silicon clusters: depressed thermal stabilities, coexisting isomers, reversible dynamical pathways and fragmentation channels - Joshi, Krati; Maibam, Ashakiran; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Silicon carbide clusters are significant due to their predominant occurrence in meteoric star dust, particularly in carbon-rich asymptotic giant branch stars. Of late, they have also been recognized as nanoclusters with potential applications in technology. Them both being elements of the same group, there is excellent potential for precise control over the physico-chemical properties of such molecular length-scale materials through atomic engineering and this has been explored recently by various experimentalists. This report simulates one of the significant physical properties, viz. conformational stability, of various carbon-doped silicon clusters as a function of temperature using Born-Oppenheimer molecular dynamics methodology. Single carbon atom-doped silicon clusters with 4-9 atoms (i.e., Si3C-Si8C) are chosen for this study as the gas phase geometries of these clusters have been characterized using a combination of experimental and theoretical methods in the recent past. The simulations ratify that various conformations do not interconvert among themselves at 300 K. The interconversion occurs at 500 K or above, thereby ratifying the possibility of the coexistence of multiple conformations of a given cluster, which are generally synthesized under subroom temperature conditions. Furthermore, the above single carbon atom-doped silicon clusters: (a) have depressed thermal stabilities as compared to their pristine counterparts with the exception of a Si5C conformation; (b) undergo multifarious evolution of the cluster, through the reversible dynamical and fragmentation pathways as a function of temperature and (c) single carbon atom-doped silicon clusters with 7 atoms (starting from Si6C) and above undergo a fragmentation at nearly 2000 K. The underlying electronic and structural properties of various clusters are discussed to explain the above observations with a note on critical fragmentation energy barriers required for the segmentation of clusters with seven or more atoms.